ALTERNATIF KAROTENOID SINTETIS (ASTAXANTIN) UNTUK MENINGKATKAN KUALITAS WARNA IKAN KOKI (Carassius auratus) - Sukarman Sukarman; Rina Hirnawati (Pusbindiklat - LIPI, 2014)
Any deficiency of carotenoid in goldfish’ feeds can fade the color of the fish (Carassius auratus), especially in aquarium condition. The aim of this study was to explore other sources of carotenoid which is to replace the synthetic carotenoid already used. The fish were fed with different types of feed i.e. those without carotenoid source (A), those with synthetic astaxanthin (synthetic carotenoid) (B), Haematococcus pluvialis meal (C), and marigold petal meal (D). Lightness (L), chroma (C), hue (H), and the content of total carotenoids in the skin of fish were analyzed. The result showed that lightness was not significantly different among treatments. The best value of chroma was 35.59% (D), significantly different from those with other treatments and followed by 25.25% (B), 20.36% (C), and 19.98% (A). The highest content of total carotenoid in the skin was derived from B (59.55mg/kg), followed by D (24.79mg/kg), C (6.84mg/kg), and A (5.37mg/kg). This study suggests that marigold petal can be used as an alternative natural carotenoid source replacing synthetic carotenoid.